Resin composition, molded article and slide member
Patent Information
- Application Number
- JP2023135578
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-03-07
AI Technical Summary
【0014】 本開示によれば、液晶ポリエステル樹脂を含有し、腐食性ガスの発生が抑制され、かつ、耐摩耗性が維持された成形品を得られる樹脂組成物を提供することができる。 また、本開示によれば、高温多湿な条件下で耐摩耗性が維持される成形品、及びこの成形品を含む摺動部材を提供することができる。
Smart Images

Figure 2025030358000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a resin composition, a molded article, and a sliding member. [Background technology]
[0002] It is known that a molded article made from a resin composition containing a liquid crystal polyester resin and a fluororesin undergoes little dimensional change even when a constant load is continuously applied to the molded article. Patent Document 1 discloses a liquid crystal polyester resin composition containing, relative to 100 parts by weight of liquid crystal polyester, 5 to 180 parts by weight of at least one compound selected from oxides, peroxides, double oxides and carbonates of metal elements belonging to Group 1A or 2A of the short periodic table, and 0.1 to 80 parts by weight of a fluororesin. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-25402 Summary of the Invention [Problem to be solved by the invention]
[0004] Industrial products and their materials are sometimes transported by sea. For example, when a ship passes through the equator on its route, the inside of the ship's container is said to be in a hotter and more humid environment than the outside air (for example, 40°C or higher and 80% or higher relative humidity). However, in the case of a molded article using the liquid crystal polyester resin composition described in Patent Document 1 as a molding material, there is a problem that corrosive gases are generated from the molded article and the molded article is easily worn under high temperature and high humidity conditions, such as when a ship passes through the equator during transportation.
[0005] The present disclosure has been made in view of the above circumstances, and aims to provide a resin composition containing a liquid crystal polyester resin, which can provide a molded article that suppresses the generation of corrosive gas and maintains abrasion resistance, and also aims to provide a molded article containing the resin composition, and a sliding member containing the molded article. [Means for solving the problem]
[0006] In order to solve the above problems, the present disclosure includes the following aspects.
[0007] [1] A resin composition containing a liquid crystal polyester resin, a fluororesin, and an oxide of a metal element belonging to Group 2 of the long form periodic table, and not containing a fibrous filler, A resin composition, wherein the content of the metal element belonging to Group 2 is 0.01% by mass or more and 2.0% by mass or less relative to 100% by mass of the total mass of the resin composition.
[0008] [2] The resin composition according to [1], wherein the content of the metal element belonging to Group 2 relative to 100 parts by mass of the fluororesin is 0.04 parts by mass or more and 8 parts by mass or less.
[0009] [3] The resin composition according to [1] or [2], wherein the content of the oxide of the metal element belonging to Group 2 is more than 0.01 mass% and less than 3.0 mass% relative to the total mass of the resin composition (100 mass%).
[0010] [4] The resin composition according to any one of [1] to [3], wherein the content of the fluororesin is 10 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the liquid crystal polyester resin.
[0011] [5] The resin composition according to any one of [1] to [4], wherein the metal element belonging to Group 2 is at least one selected from the group consisting of calcium and magnesium. [6] The resin composition according to [5], wherein the metal element belonging to Group 2 is calcium.
[0012] [7] The resin composition according to any one of [1] to [6], wherein the liquid crystal polyester resin has a repeating unit represented by the following formula (1), a repeating unit represented by the following formula (2), and a repeating unit represented by the following formula (3): (1)-O-Ar 1 -CO- (2)-CO-Ar 2 -CO- (3)-X-Ar 3 -Y- [In formulas (1) to (3), Ar 1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar 2 and Ar 3 each independently represents a phenylene group, a naphthylene group, a biphenylylene group, or a group represented by the following formula (4), and X and Y each independently represent an oxygen atom or an imino group (-NH-). 1 , Ar 2 Or Ar 3 One or more hydrogen atoms in the group represented by the following formula may be substituted, independently of one another, with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.] (4)-Ar 4 -Z-Ar 5 - [In formula (4), Ar 4 and Ar 5 each independently represents a phenylene group or a naphthylene group, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylidene group having 1 to 10 carbon atoms. 4 Or Ar 5 One or more hydrogen atoms in the group represented by the following formula may be substituted, independently of one another, with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.]
[0013] [8] A molded article comprising the resin composition according to any one of [1] to [7] above. [9] A sliding member comprising the molded article according to [8] above. Effect of the Invention
[0014] According to the present disclosure, it is possible to provide a resin composition that contains a liquid crystal polyester resin, and that can give a molded article that suppresses the generation of corrosive gases and maintains abrasion resistance. Furthermore, according to the present disclosure, it is possible to provide a molded article that maintains its abrasion resistance under high-temperature and high-humidity conditions, and a sliding member that includes this molded article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] (Resin composition) One embodiment of the resin composition contains a liquid crystal polyester resin, a fluororesin, and an oxide of a metal element belonging to Group 2 of the long form periodic table, does not contain a fibrous filler, and has a content of the metal element belonging to Group 2 of 0.01 mass % or more and 2.0 mass % or less with respect to 100 mass % of the total mass of the resin composition.
[0016] In this specification, the term "resin composition" refers to a mixture obtained by mixing a liquid crystal polyester resin, a fluororesin, an oxide of a metal element belonging to Group 2 of the long periodic table, and, if necessary, other components. The resin composition may be in the form of pellets.
[0017] Since the resin composition in this embodiment does not contain a fibrous filler, the resin composition is unlikely to damage the mating material that comes into contact with the sliding member containing the resin composition, even if the mating material is a soft metal (for example, SUS or aluminum).
[0018] <Liquid crystal polyester resin> The liquid crystal polyester resin is not particularly limited as long as it is a polyester resin that exhibits liquid crystallinity in a molten state. The liquid crystal polyester resin is preferably one that melts at a temperature of 450° C. or less.
[0019] The flow initiation temperature of the liquid crystal polyester resin is preferably 250° C. or higher, more preferably 270° C. or higher, and even more preferably 280° C. or higher. The flow initiation temperature of the liquid crystal polyester resin is preferably 400° C. or lower, more preferably 360° C. or lower, and even more preferably 340° C. or lower. For example, the flow initiation temperature of the liquid crystal polyester resin is preferably 250°C or more and 400°C or less, more preferably 270°C or more and 360°C or less, and further preferably 280°C or more and 340°C or less.
[0020] In this specification, the flow initiation temperature of the liquid crystal polyester resin is measured by compressing the liquid crystal polyester resin at 9.8 MPa (100 kg / cm) using a flow tester. 2 When the liquid crystal polyester resin is melted under a load of 1000 g / mol and heated at a rate of 4°C / min and extruded from a nozzle with an inner diameter of 1 mm and a length of 10 mm, the liquid crystal polyester resin shows a viscosity of 4800 Pa·s (48,000 poise).
[0021] The liquid crystal polyester resin is preferably a wholly aromatic liquid crystal polyester having only repeating units derived from aromatic compounds.
[0022] In this specification, the term "derived from" means that in the polymerization of the raw material monomer, the chemical structure of the functional group that contributes to the polymerization is changed, and other chemical structures are not changed. The term "derived from" as used herein is a concept that also includes cases where the derived from a polymerizable derivative of the raw material monomer.
[0023] Examples of polymerizable derivatives of compounds having a carboxy group, such as aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids, include esters in which the carboxy group is converted to an alkoxycarbonyl group or an aryloxycarbonyl group; acid halides in which the carboxy group is converted to a haloformyl group; acid anhydrides in which the carboxy group is converted to an acyloxycarbonyl group; and the like.
[0024] Examples of polymerizable derivatives of compounds having a hydroxy group, such as aromatic hydroxycarboxylic acids, aromatic diols and aromatic hydroxyamines, include acylation products in which the hydroxy group is acylated to convert it into an acyloxyl group. Examples of polymerizable derivatives of compounds having an amino group, such as aromatic hydroxyamines and aromatic diamines, include acylated products in which the amino group is acylated to convert it into an acylamino group.
[0025] The liquid crystal polyester resin preferably has a repeating unit represented by the following formula (1) (hereinafter also referred to as "repeating unit (1)"), and more preferably has the repeating unit (1), a repeating unit represented by the following formula (2) (hereinafter also referred to as "repeating unit (2)"), and a repeating unit represented by the following formula (3) (hereinafter also referred to as "repeating unit (3)").
[0026] (1)-O-Ar 1 -CO- (2)-CO-Ar 2 -CO- (3)-X-Ar 3 -Y- [In formulas (1) to (3), Ar 1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar 2 and Ar 3 each independently represents a phenylene group, a naphthylene group, a biphenylylene group, or a group represented by the following formula (4), and X and Y each independently represent an oxygen atom or an imino group (-NH-). 1 , Ar 2 Or Ar 3 One or more hydrogen atoms in the group represented by the following formula may be substituted, independently of one another, with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.]
[0027] (4)-Ar 4 -Z-Ar 5 - [In formula (4), Ar 4 and Ar 5each independently represents a phenylene group or a naphthylene group, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylidene group having 1 to 10 carbon atoms. 4 Or Ar 5 One or more hydrogen atoms in the group represented by the following formula may be substituted, independently of one another, with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.]
[0028] Ar 1 , Ar 2 , Ar 3 , Ar 4 Or Ar 5 Examples of the halogen atom which can substitute for a hydrogen atom in include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.
[0029] Ar 1 , Ar 2 , Ar 3 , Ar 4 Or Ar 5 The alkyl group which can substitute for a hydrogen atom in is an alkyl group having 1 to 10 carbon atoms, and examples of such groups include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a s-butyl group, a t-butyl group, an n-hexyl group, a 2-ethylhexyl group, an n-octyl group, and an n-decyl group. The alkyl group may be linear or branched.
[0030] Ar 1 , Ar 2 , Ar 3 , Ar 4 Or Ar 5 The aryl group which can replace the hydrogen atom of is an aryl group having 6 to 20 carbon atoms, and examples thereof include a phenyl group, an o-tolyl group, an m-tolyl group, a p-tolyl group, a 1-naphthyl group, and a 2-naphthyl group. The aryl group may be a single ring or a condensed ring. The aryl group may be a group in which a hydrogen atom of an aromatic ring is replaced with an alkyl group, such as a tolyl group.
[0031] Ar 1 , Ar 2 , Ar3 , Ar 4 Or Ar 5 When a hydrogen atom of is substituted with the above-mentioned group, the number of substitutions is preferably 1 or 2, and more preferably 1.
[0032] The alkylidene group for Z in formula (4) is an alkylidene group having 1 to 10 carbon atoms, and examples thereof include a methylene group, an ethylidene group, an isopropylidene group, an n-butylidene group, and a 2-ethylhexylidene group.
[0033] The repeating unit (1) is Ar 1 A repeating unit in which R is a 1,4-phenylene group or a repeating unit in which R is a 2,6-naphthylene group is preferred.
[0034] The repeating unit (2) is Ar 2 is preferably a repeating unit in which Ar is a 1,4-phenylene group, a 1,3-phenylene group, a 2,6-naphthylene group, a 2,7-naphthylene group, a 4,4'-biphenylylene group, or a diphenylether-4,4'-diyl group; 2 More preferred are repeating units in which R is a 1,4-phenylene group, a 1,3-phenylene group, or a 2,6-naphthylene group.
[0035] The repeating unit (3) is Ar 3 A repeating unit in which R is a 1,4-phenylene group or a repeating unit in which R is a 4,4'-biphenylylene group is preferred.
[0036] The repeating unit (3) preferably has a repeating unit in which X and Y are each an oxygen atom, since this tends to reduce the melt viscosity of the liquid crystal polyester resin. It is more preferable that the repeating unit (3) contains only repeating units in which X and Y are each an oxygen atom.
[0037] More specifically, the liquid crystal polyester resin having the above repeating units (1) to (3) preferably has a repeating unit represented by the following formula (11) (hereinafter also referred to as "repeating unit (11)"), a repeating unit represented by the following formula (12) (hereinafter also referred to as "repeating unit (12)"), and a repeating unit represented by the following formula (13) (hereinafter also referred to as "repeating unit (13)").
[0038] (11)-O-Ar 11 -CO- (12)-CO-Ar 12 -CO- (13)-O-Ar 13 -O- [In formulas (11) to (13), Ar 11 represents a 2,6-naphthylene group or a 1,4-phenylene group. 12 represents a 2,6-naphthylene group, a 2,7-naphthylene group, a 1,4-phenylene group, a 1,3-phenylene group, a 4,4'-biphenylylene group, or a diphenylether-4,4'-diyl group. 13 represents a 1,4-phenylene group or a 4,4'-biphenylylene group. 11 , Ar 12 Or Ar 13 One or more hydrogen atoms in the group represented by the following formula may be substituted, independently of one another, with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.]
[0039] As a preferred liquid crystal polyester resin having the repeating units (11) to (13), there is provided Ar 11 A repeating unit (11) in which is a 1,4-phenylene group, and Ar 12 A repeating unit (12) in which Ar is a 1,4-phenylene group, 12 A repeating unit (12) in which is a 1,3-phenylene group, and Ar 13 and a repeating unit (13) in which the repeating unit is a 4,4'-biphenylylene group.
[0040] The number of repeating units (1) is preferably 30% or more and 80% or less, more preferably 40% or more and 70% or less, and even more preferably 45% or more and 70% or less, of the total number of all repeating units constituting the liquid crystal polyester resin (100%) (hereinafter referred to as "total number of all repeating units").
[0041] The number of repeating units (2) is preferably from 10% to 35%, more preferably from 15% to 30%, and even more preferably from 15% to 27.5%, of the total number of all repeating units.
[0042] The number of repeating units (3) is more preferably from 10% to 35%, more preferably from 15% to 30%, and even more preferably from 15% to 27.5%, of the total number of all repeating units.
[0043] In the liquid crystal polyester resin having repeating units (1) to (3), for example, the number of repeating units (1) is preferably 30% or more and 80% or less of the total number of all repeating units, and the number of repeating units (2) and the number of repeating units (3) are each preferably 10% or more and 35% or less of the total number of all repeating units.
[0044] In addition, it is more preferable that the liquid crystal polyester resin has a number of repeating units (1) of 40% or more and 70% or less of the total number of all repeating units, and that the number of repeating units (2) and the number of repeating units (3) are both 15% or more and 30% or less of the total number of all repeating units.
[0045] Furthermore, it is particularly preferable that the liquid crystal polyester resin has a number of repeating units (1) of 45% or more and 70% or less of the total number of all repeating units, and the number of repeating units (2) and the number of repeating units (3) are both 15% or more and 27.5% or less of the total number of all repeating units.
[0046] The ratio of the content of repeating units (2) to the content of repeating units (3), expressed as [the number of repeating units (2)] / [the number of repeating units (3)], is preferably from 0.9 / 1 to 1 / 0.9, more preferably from 0.95 / 1 to 1 / 0.95, and even more preferably from 0.98 / 1 to 1 / 0.98.
[0047] The liquid crystal polyester resin may have two or more kinds of each of the repeating units (1), (2), and (3). The liquid crystal polyester resin may have repeating units other than the repeating units (1), (2), and (3), but the number of such repeating units is preferably 10% or less, more preferably 5% or less, based on the total number of all repeating units.
[0048] In a liquid crystal polyester resin having repeating units (1), (2), and (3), the sum of the content of repeating units (1), (2), and (3) does not exceed 100%.
[0049] In this specification, the number of each repeating unit constituting the liquid crystal polyester resin is determined by the analysis method described in JP-A-2000-19168. Specifically, the liquid crystal polyester resin is depolymerized by reacting it with a lower alcohol in a supercritical state, and the depolymerization products (monomers that derive each repeating unit) are quantified by liquid chromatography, whereby the number of each repeating unit relative to the total repeating units can be calculated.
[0050] The resin composition may contain one type of liquid crystal polyester, or may contain two or more types of liquid crystal polyesters.
[0051] The liquid crystal polyester resin can be produced by melt-polymerizing raw material monomers corresponding to the repeating units constituting the liquid crystal polyester resin, and then solid-phase polymerizing the obtained polymer. For example, the liquid crystal polyester resin can be produced by a production method including the following acylation step and polymerization step, such as the method described in Japanese Patent No. 6439027.
[0052] Acylation step: A step of obtaining an acylated product by acylating the phenolic hydroxyl group of the raw material monomer with a fatty acid anhydride (e.g., acetic anhydride, etc.). Polymerization step: A step of obtaining a liquid crystal polyester resin by polymerizing the acyl group of the acylation product with the carboxyl group of the acylation product of an aromatic dicarboxylic acid and an aromatic hydroxycarboxylic acid so as to cause transesterification.
[0053] <Fluororesin> In this specification, the term "fluororesin" refers to a resin containing fluorine atoms in the molecule, and includes polymers having a structural unit containing a fluorine atom. Examples of the fluororesin contained in the resin composition of this embodiment include polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), polychlorotrifluoroethylene (PCTFE), ethylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride (PVDF), and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (perfluoroalkoxyalkane, PFA). Among these, the fluororesin is preferably polytetrafluoroethylene (PTFE) from the viewpoints of excellent miscibility with the liquid crystal polyester resin, and excellent sliding properties and heat resistance of the molded product. The resin composition may contain one type of fluororesin, or may contain two or more types of fluororesin.
[0054] <Oxides of metal elements belonging to Group 2 of the long-form periodic table> The resin composition of the present embodiment contains an oxide of a metal element belonging to Group 2 of the long periodic table. Metal elements belonging to Group 2 include beryllium, magnesium, calcium, strontium, barium, and radium. An oxide of any of magnesium, calcium, strontium, barium, and radium that can react with water is preferred. In this embodiment, the metal element belonging to Group 2 is preferably at least one selected from the group consisting of calcium and magnesium, and more preferably calcium, in order to further suppress the generation of corrosive gas from the molded article. The oxide contained in the resin composition of this embodiment is preferably at least one selected from the group consisting of calcium oxide and magnesium oxide, and more preferably calcium oxide. The resin composition may contain one type of the oxide, or may contain two or more types of the oxide.
[0055] The content of the liquid crystal polyester resin relative to the total mass (100 mass%) of the resin composition of this embodiment may be more than 57 mass% and less than 89.99 mass%, more than 57 mass% and less than 89.9 mass%, more than 62 mass% and less than 84.9 mass%, or 67.5 mass% or more and 79.5 mass% or less.
[0056] The content of the fluororesin relative to the total mass (100 mass%) of the resin composition of this embodiment may be 10 mass% or more and 40 mass% or less, 15 mass% or more and 35 mass% or less, or 20 mass% or more and 30 mass% or less.
[0057] The content of the oxide of the metal element belonging to the second group relative to the total mass (100 mass%) of the resin composition of this embodiment is preferably more than 0.01 mass% and less than 3.0 mass%, more preferably 0.1 mass% or more and less than 3.0 mass%, even more preferably more than 0.1 mass% and less than 3.0 mass%, and particularly preferably 0.5 mass% or more and 2.5 mass% or less. When the content of the oxide of the metal element belonging to Group 2 is equal to or more than the lower limit of the above-mentioned preferred range, the generation of corrosive gas from the molded article is easily suppressed, whereas when the content is equal to or less than the upper limit of the above-mentioned preferred range, the wear resistance of the molded article is easily maintained.
[0058] Furthermore, the content of the oxide of the metal element belonging to the second group relative to the total mass (100 mass%) of the resin composition of this embodiment is preferably 0.1 mass% or more and 2 mass% or less, and particularly preferably 0.5 mass% or more and 2 mass% or less. When the content of the oxide of a metal element belonging to Group 2 is equal to or greater than the lower limit of the preferred range, the generation of corrosive gas from the molded article is easily suppressed. On the other hand, when the content is equal to or less than the upper limit of the preferred range, the abrasion resistance of the molded article is easily maintained under high temperature and high humidity conditions, and the color change of the resin composition is also more unlikely to occur.
[0059] The content of the metal element belonging to the second group relative to the total mass (100 mass%) of the resin composition of this embodiment is 0.01 mass% or more and 2.0 mass% or less, preferably 0.05 mass% or more and 2.0 mass% or less, more preferably 0.1 mass% or more and 2.0 mass% or less, and even more preferably 0.3 mass% or more and 1.8 mass% or less. When the content of the metal element belonging to Group 2 is equal to or more than the lower limit of the preferred range, the generation of corrosive gas from the molded article is easily suppressed, whereas when the content is equal to or less than the upper limit of the preferred range, the wear resistance of the molded article is easily maintained.
[0060] Furthermore, the content of the metal element belonging to the second group relative to the total mass (100 mass%) of the resin composition of this embodiment is preferably 0.05 mass% or more and 1.5 mass% or less, and particularly preferably 0.3 mass% or more and 1.5 mass% or less. When the content of the metal element belonging to Group 2 is equal to or greater than the lower limit of the preferred range, the generation of corrosive gas from the molded article is easily suppressed, whereas when the content is equal to or less than the upper limit of the preferred range, the abrasion resistance of the molded article is easily maintained under high temperature and high humidity conditions, and the appearance of the resin composition is less likely to change.
[0061] In this specification, the content of the metal element belonging to Group 2 relative to the total mass (100 mass %) of the resin composition is defined as a value measured by the following measurement method.
[0062] [Method for measuring the content of metal elements belonging to Group 2 in a resin composition] The resin composition is heated at a temperature of, for example, 500 to 700° C. to remove the resin component, and the metal element content of the resulting residue can be measured by a known method. A preferred method for measuring the metal element content is, for example, inductively coupled plasma mass spectrometry (ICP-MS), which can be used for highly sensitive measurement.
[0063] In the resin composition of this embodiment, the content of the fluororesin relative to 100 parts by mass of the liquid crystal polyester resin may be 10 parts by mass or more and 50 parts by mass or less, may be 20 parts by mass or more and 45 parts by mass or less, or may be 30 parts by mass or more and 40 parts by mass or less.
[0064] In the resin composition of this embodiment, the content of the oxide of the metal element belonging to Group 2 relative to 100 parts by mass of the liquid crystal polyester resin may be 0.1 parts by mass or more and 4 parts by mass or less, may be 0.2 parts by mass or more and 3.5 parts by mass or less, or may be 0.5 parts by mass or more and 3 parts by mass or less.
[0065] In the resin composition of this embodiment, the content of the metal element belonging to the second group relative to 100 parts by mass of the liquid crystal polyester resin may be 0.05 parts by mass or more and less than 3 parts by mass, 0.2 parts by mass or more and 2.5 parts by mass or less, or 0.4 parts by mass or more and 2 parts by mass or less.
[0066] In the resin composition of this embodiment, the content of the oxide of the metal element belonging to Group 2 relative to 100 parts by mass of the fluororesin may be 0.3 parts by mass or more and less than 12 parts by mass, 0.5 parts by mass or more and 11 parts by mass or less, or 1 part by mass or more and 10 parts by mass or less. When the content of the oxide of the metal element belonging to Group 2 is equal to or more than the lower limit of the above-mentioned preferred range, the generation of corrosive gas from the molded article is easily suppressed, whereas when the content is equal to or less than the upper limit of the above-mentioned preferred range, the wear resistance of the molded article is easily maintained.
[0067] Furthermore, in the resin composition of this embodiment, the content of the oxide of the metal element belonging to the second group relative to 100 parts by mass of the fluororesin is preferably 0.4 parts by mass or more and 9 parts by mass or less, and particularly preferably 1.5 parts by mass or more and 9 parts by mass or less. When the content of the oxide of the metal element belonging to the second group is equal to or more than the lower limit of the above-mentioned preferred range, the generation of corrosive gas from the molded article is easily suppressed, while when it is equal to or less than the upper limit of the above-mentioned preferred range, the wear resistance of the molded article is easily maintained under high temperature and high humidity conditions, and the appearance of the resin composition is less likely to change.
[0068] In the resin composition of this embodiment, the content of the metal element belonging to Group 2 relative to 100 parts by mass of the fluororesin is preferably 0.04 parts by mass or more and 8 parts by mass or less, more preferably 0.2 parts by mass or more and 8.5 parts by mass or less, even more preferably 0.4 parts by mass or more and 8 parts by mass or less, and particularly preferably 1 part by mass or more and 7.5 parts by mass or less. When the content of the metal element belonging to Group 2 is equal to or more than the lower limit of the preferred range, the generation of corrosive gas from the molded article is easily suppressed, whereas when the content is equal to or less than the upper limit of the preferred range, the wear resistance of the molded article is easily maintained.
[0069] Furthermore, in the resin composition of this embodiment, the content of the metal element belonging to Group 2 relative to 100 parts by mass of the fluororesin is preferably 0.2 parts by mass or more and 6 parts by mass or less, and particularly preferably 1.4 parts by mass or more and 6 parts by mass or less. When the content of the metal element belonging to Group 2 is equal to or greater than the lower limit of the preferred range, the generation of corrosive gas from the molded article is easily suppressed, whereas when the content is equal to or less than the upper limit of the preferred range, the abrasion resistance of the molded article is easily maintained under high temperature and high humidity conditions, and the appearance of the resin composition is less likely to change.
[0070] In the resin composition of the present embodiment, the contents of the liquid crystal polyester resin, the fluororesin, and the oxide of the metal element belonging to Group 2 of the long periodic table can be adjusted to the above-mentioned contents by adjusting the blending amounts of each raw material when preparing the resin composition. In the resin composition of this embodiment, the content of the metal element belonging to the second group can be controlled to the above-mentioned preferred content by adjusting the blending amount of the oxide of the corresponding metal element belonging to the second group when preparing the resin composition.
[0071] <Fibrous filler> The resin composition of the present embodiment does not contain a fibrous filler. In this specification, the phrase "containing no fibrous filler" means that the content of the fibrous filler is from 0% by mass to 1% by mass, both inclusive, relative to 100% by mass of the total mass of the resin composition.
[0072] The fibrous filler may be an inorganic filler or an organic filler. Examples of the fibrous inorganic filler include glass fibers, modified cross-section glass fibers, carbon fibers, silica fibers, alumina fibers, ceramic fibers, metal fibers, silicon carbide fibers, and whiskers. Examples of fibrous organic fillers include polyester fibers; para- or meta-aramid fibers; and polyparaphenylene benzobisoxazole (PBO) fibers.
[0073] <Other ingredients> The resin composition of the present embodiment may contain, in addition to the above-mentioned liquid crystal polyester resin, fluororesin, and oxide of a metal element belonging to Group 2 of the long form periodic table, any other components other than these. Examples of other components include fillers other than fibrous fillers, other resins other than liquid crystal polyester resin and fluororesin, flame retardants, electrical conductivity imparting agents, crystal nucleating agents, ultraviolet absorbers, antioxidants, vibration dampers, antibacterial agents, insect repellents, deodorants, coloration inhibitors, heat stabilizers, release agents, antistatic agents, plasticizers, lubricants, dyes, foaming agents, foam control agents, viscosity adjusters, surfactants, and the like.
[0074] <Filling agent> Examples of fillers other than fibrous fillers include plate-like fillers, spherical fillers, and powder fillers. Examples of the plate-like filler include talc, mica, glass flakes, graphite, etc. The plate-like filler may be surface-treated or untreated. Examples of the mica include natural mica such as muscovite, phlogopite, fluorine phlogopite, and tetrasilicic mica, and synthetic mica that is artificially produced. Examples of the spherical filler include glass beads and glass balloons. Examples of powder fillers include calcium carbonate, dolomite, clay barium sulfate, titanium oxide, carbon black, conductive carbon, and fine silica. The resin composition of the present embodiment may contain a filler other than a fibrous filler. However, from the viewpoint of preventing damage to the counter material with which the sliding member comes into contact, it is preferable that the resin composition does not contain a filler other than a fibrous filler. In this specification, the phrase "containing no filler other than fibrous filler" means that the content of the filler is from 0% by mass to 1% by mass with respect to 100% by mass of the total mass of the resin composition.
[0075] <Other resins other than liquid crystal polyester resin and fluororesin> Other resins include polyolefin resins, vinyl resins, polystyrene resins, polyamide resins, polyester resins, polysulfone resins, polyphenylene sulfide, polyether ketone, polycarbonate, polyphenylene ether, and polyimide resins.
[0076] In the resin composition of this embodiment, the content of other resins other than the liquid crystal polyester resin and the fluororesin relative to the total mass of the resin composition (100 mass%) is preferably 10 mass% or less, more preferably 5 mass% or less, and even more preferably 1 mass% or less. It is particularly preferable that the resin composition of this embodiment does not contain other resins.
[0077] In the resin composition of the present embodiment, the content of the metal element belonging to the second group is 0.01% by mass or more relative to the total mass (100% by mass) of the resin composition, so that the generation of corrosive gas from the molded article is suppressed. In addition, the content of the metal element belonging to the second group is 2.0% by mass or less, so that a molded article that maintains abrasion resistance, particularly under high temperature and high humidity conditions, can be provided.
[0078] The corrosive gases generated from the molded products are believed to be due to the thermal decomposition of the resin composition during molding processing at temperatures exceeding 300°C, and it has been confirmed that they are mainly gases such as acetic acid, phenol, and aromatic esters. It is presumed that in the resin composition, the oxide of the metal element belonging to Group 2 acts as a basic compound and exerts the effect of capturing mainly acetic acid, thereby suppressing the generation of corrosive gases from the molded article.
[0079] If a hydroxide of a metal element belonging to Group 2 is present in the resin composition, it may affect the stability of the structure constituting the molded article, resulting in deterioration of abrasion resistance and / or a change in color, and therefore it is preferable that the content of the hydroxide is small. The content of the hydroxide of the metal element belonging to Group 2 is preferably 0.5% by mass or less, more preferably 0.4% by mass or less, and even more preferably 0.3% by mass or less, based on 100% by mass of the total mass of the resin composition. For example, the content of the hydroxide of the metal element belonging to Group 2 may be 0% by mass or more and 0.4% by mass or less, or 0.1% by mass or more and 0.3% by mass or less, based on 100% by mass of the total mass of the resin composition.
[0080] In addition, in the resin composition of the present embodiment, by controlling the upper limit of the content of the metal element belonging to Group 2, the color difference ΔE of the resin composition can be kept small under high temperature and high humidity conditions, making it difficult for a change in color to occur.
[0081] (molded product) One embodiment of the molded article is a molded article containing the resin composition of the above-described embodiment. The molded product of this embodiment can be obtained by a known molding method using the resin composition. As a molding method using the resin composition of the above embodiment, a melt molding method is preferable, and examples thereof include an injection molding method, an extrusion molding method such as a T-die method or an inflation method, a compression molding method, a blow molding method, a vacuum molding method, and a press molding method. Among them, the injection molding method is preferable.
[0082] For example, a molded article can be obtained by melting the resin composition of the embodiment using a known injection molding machine and injecting the molten resin composition into a mold. Examples of known injection molding machines include TR450EH3 manufactured by Sodick Co., Ltd., and hydraulic horizontal molding machine PS40E5ASE type and ES400 manufactured by Nissei Plastic Industrial Co., Ltd.
[0083] Regarding the temperature conditions for injection molding, the cylinder temperature of the injection molding machine is preferably set to a temperature 10 to 80° C. higher than the flow initiation temperature of the resin composition used. The temperature of the mold is preferably set in the range of 25° C. to 180° C. from the viewpoints of the time required for cooling the resin composition and productivity. Other injection conditions such as the screw rotation speed, back pressure, injection speed, pressure holding, and pressure holding time may be appropriately adjusted.
[0084] Since the molded article of the present embodiment uses the above-mentioned resin composition, the wear resistance is maintained in a high-temperature environment, and the generation of corrosive gas is suppressed. The molded article of the present embodiment is useful for, for example, damper rings, oil seals, piston rings, etc.
[0085] (Sliding member) One embodiment of the slide member is a slide member including the molded article of the above-described embodiment. The sliding member of this embodiment is suitable for use in, for example, dampers and bearings, and is particularly suitable as an automobile part from the viewpoints that wear resistance is maintained and generation of corrosive gas is suppressed. EXAMPLES
[0086] The present disclosure will be described below with reference to examples, but the present disclosure is not limited to these examples.
[0087] [Measurement of the content of metal elements belonging to Group 2 in a resin composition] The content of metal elements in the resin composition was determined by heating the resin composition at 600° C. and measuring the resulting residue by inductively coupled plasma mass spectrometry (ICP-MS).
[0088] [Measurement of flow start temperature of liquid crystal polyester resin and pellets] The liquid crystal polyester resin and the pellet-like resin composition were each used as a sample. First, using a flow tester (Shimadzu Corporation, CFT-500 model), about 2 g of sample was filled into a cylinder equipped with a die having a nozzle with an inner diameter of 1 mm and a length of 10 mm. Next, 9.8 MPa (100 kg / cm 2 The sample was melted and extruded from the nozzle while being heated at a rate of 4°C / min under a load of 1000 g / s (1000 psi), and the temperature at which the sample showed a viscosity of 4800 Pa s (48,000 poise) was measured and used as the temperature at which the sample began to flow.
[0089] [Measurement of pellet brightness and color] Using a color difference meter ("CM-3600A" manufactured by Konica Minolta, Inc.), the lightness (L*: SCE method) and chromaticity (a*, b*: SCE method) of the pellets were measured according to the L*a*b* color system without cutting off ultraviolet light under the conditions of an illumination and receiving optical system of D65, C light source, observation field of view of 10°, and measurement diameter of 25.4 mm.
[0090] [Measurement of the amount of acetic acid generated from pellets] 4 g of pellets of the liquid crystal polyester resin composition were weighed out, washed with distilled water, and then placed in a vacuum-dried 25 cc vial. The vial was sealed with a packing made of polytetrafluoroethylene and then heated in a hot air dryer set at 150°C for 20 hours. The sealed vial was attached to a headspace gas chromatograph (GC-15A / HSS-3A) manufactured by Shimadzu Corporation. After the vial was kept at a temperature of 150°C for 1 hour, the vial was injected into a 15 m long column containing DBWAX (manufactured by J&W SCIENTIFIC) as a packing material. Simultaneously with the injection of the vial, the column temperature was raised from 80°C at 2°C / min, and the gas was detected with a detector up to a retention time of 25 minutes. An FID type detector was used, and helium was used as the carrier gas. From the detected gas peaks, the amount of acetic acid in the gas generated from the pellets was calculated based on the peak at the retention time of acetic acid, which had been confirmed in advance using a standard substance.
[0091] [Measurement of surface roughness Ra and wear amount of molded products] The surface roughness Ra of the molded article defined in JIS B0601-2001 was measured using a 3D scanner-type coordinate measuring machine (manufactured by KEYENCE Corporation). Measurements were performed at least four different points on each molded article, and the arithmetic mean value was calculated. For the molded products whose surface roughness Ra was measured, the amount of wear of each molded product was determined by the sliding test described below using a Suzuki-type friction and wear tester (EFM-3-HS, manufactured by A&D Co., Ltd.) (ring-on-disc).
[0092] Sliding test: A silicone oil with a kinetic viscosity of 450 to 600 Pa s at 25°C was applied to the molded product, and a metal ring was placed on top of the molded product. The test was continued for 24 hours in a constant temperature bath at 120°C, with a load of 105 N applied to the metal ring and the molded product rotated at 123 rpm.
[0093] The specific test conditions were as follows: Metal ring: SUS304 (Ra: 0.02mm or less) Rotational speed of molded product: 0.15m / s Measurement temperature: 120℃ Contact area between metal ring and molded product: 2.0cm 2
[0094] After the sliding test, the molded product was removed and cooled to room temperature. After the silicone oil adhering to the surface of the cooled molded product was wiped off, the maximum surface roughness Rt of the sliding surface, as defined by JIS B0601-2001, was measured using a 3D scanner-type coordinate measuring machine (manufactured by KEYENCE Corporation). Measurements were performed at least four different points for each molded product, and the arithmetic mean value was calculated. The amount of wear of the molded product was calculated using the following formula.
[0095] Wear of molded product (m 3 / m) = {Maximum surface roughness Rt (μm) × 2.0 (cm 2 ) x 10 -6 (m / μm)×10 -4 (m 2 / cm 2 )} / {0.15(m / s)×24(h)×3600(s / h)})
[0096] In the above sliding test, the greater the maximum surface roughness after the test, the deeper the surface has been worn away. Therefore, the maximum surface roughness Rt (μm) is used as the standard for the amount of wear of the molded product. 2.0(cm in the numerator of the above formula 2 ) refers to the contact area between the metal ring and the molded product, and the numerator of the above formula, which is obtained by multiplying the contact area by the maximum surface roughness Rt, represents the volume of the molded product that is actually worn away. The x10 to the power of -6 and x10 to the power of -4 in the numerator of the above formula are multiplications for unit conversion. The amount of wear of the molded product depends on the test distance (i.e., the total length of contact between the molded product and the metal ring due to rotation), so in the above formula, it is normalized by dividing by the test distance. In the above sliding test, the molded product was rotated for 24 hours at a rotation speed of 0.15 (m / s), and the denominator in the above formula means the total length of contact between the molded product and the metal ring after 24 hours of continuous rotation.
[0097] The amount of wear of a molded product is an index of its sliding properties. The smaller this value, the better the sliding properties.
[0098] Liquid crystal polyester resin used Liquid Crystal Polyester (LCP) Production: In a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer and a reflux condenser, 994.5g (7.2 mol) of p-hydroxybenzoic acid, 299.0g (1.8 mol) of terephthalic acid, 99.7g (0.6 mol) of isophthalic acid, 446.9g (2.4 mol) of 4,4'-dihydroxybiphenyl and 1347.6g (13.2 mol) of acetic anhydride were put, and the gas in the reactor was replaced with nitrogen gas, after which 0.18g of 1-methylimidazole was added, and the mixture was heated from room temperature to 150°C over 30 minutes while stirring under a nitrogen gas stream, and refluxed at 150°C for 30 minutes. Next, 2.4g of 1-methylimidazole was added, and the mixture was heated from 150°C to 320°C over 2 hours and 50 minutes while distilling off by-product acetic acid and unreacted acetic anhydride, and when an increase in torque was observed, the contents were removed from the reactor and cooled to room temperature. The obtained solid was pulverized in a pulverizer, and the temperature was increased from room temperature to 250°C over 1 hour under a nitrogen gas atmosphere, then increased from 250°C to 295°C over 5 hours, and held at 295°C for 3 hours to cause solid-state polymerization. The mixture was then cooled to obtain a powdered liquid crystal polyester resin (LCP). The flow initiation temperature of the obtained liquid crystal polyester resin (LCP) was 327°C.
[0099] Fluorine resin used Polytetrafluoroethylene (product name "Dyneon (registered trademark) TF9205" manufactured by 3M Japan Ltd.).
[0100] Oxides of metal elements in Group 2 of the long-form periodic table Calcium oxide (product name "VESTA PP" manufactured by Inoue Lime Industry Co., Ltd., particle size 12 μm) and magnesium oxide (product name "Kyowamag 150" manufactured by Kyowa Chemical Industry Co., Ltd., particle size 6.9 μm).
[0101] Hydroxides of metal elements Calcium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).
[0102] <Production of Pellet-shaped Resin Composition> (Examples 1 to 7, Comparative Examples 1 to 4) The liquid crystal polyester resin composition obtained by mixing each component in the ratio shown in Table 1 was fed into a co-rotating twin-screw extruder ("PCM-30" manufactured by Ikegai Iron Works) having a screw diameter of 30 mm, melt-kneaded, and pelletized to obtain the pellet-shaped resin composition of each example.
[0103] <Measurement of pellet-shaped resin composition> Immediately after production, the pelletized resin composition of each example was measured for flow initiation temperature (° C.) and amount of corrosive gas generated (ppm). The measurement results are shown in Table 1. In addition, the brightness and chromaticity of the pellet-shaped resin composition of each example were measured immediately after production.
[0104] Next, about 10 g of the pellet-shaped resin composition of each example immediately after production was stored for 500 hours in a thermo-hygrostat (PJ-2L manufactured by Espec Corp.) at a temperature of 40° C. and a relative humidity of 90% RH. After this, the flow initiation temperature (° C.) and the brightness and chromaticity of the pellet-shaped resin composition of each example were measured in the same manner as before storage.
[0105] The amount of corrosive gas generated was evaluated by measuring the amount of acetic acid generated from the pellet-shaped resin composition. The change in color of the pellet-shaped resin composition was evaluated by calculating the color difference ΔE (SCE method) from the measured values before and after storage. These results are shown in Table 1.
[0106] The color difference ΔE is defined by the following formula: △E={(△L*) 2 +(△a*) 2 +(△b*) 2} 1 / 2 Here, ΔL*, Δa*, and Δb* are the differences in the measured values of L*, a*, and b* before and after storage, respectively.
[0107] <Production of molded products> The pellet-shaped resin composition of each example obtained above was placed in an injection molding machine ES400 (manufactured by Nissei Plastic Industrial Co., Ltd.) with a cylinder temperature of 340°C, and injected into a mold with a mold temperature of 130°C at an injection speed of 40 mm / s, a screw rotation speed of 100 rpm, a holding pressure of 50 MPa, and a back pressure of 3 MPa to produce an injection-molded test piece of 64 mm x 64 mm x 3 mm thick as a molded product.
[0108] <Evaluation of molded products> The surface roughness Ra of the molded product immediately after production, which was produced in the above <Production of molded product>, was measured. The molded product was cut to 35 mm x 35 mm x 3 mm thickness, and the amount of wear of the molded product was measured. The measurement results are shown in Table 1. The cut molded product was dried at 120° C. for 5 hours or more to remove moisture, and then the weight of the molded product was measured.
[0109] Next, the cut molded product was stored for 500 hours in a thermohygrostat (PJ-2L manufactured by Espec Corporation) at a temperature of 40°C and a relative humidity of 90%RH. After this, the surface roughness Ra (μm) and the wear amount (m 3 The results are shown in Table 1. The weight of each molded article after storage was measured. The water absorption rate (%) of the molded article was calculated based on the change in weight before and after storage using the following formula. The results are shown in Table 1. Water absorption rate of molded product (%) = {(weight of molded product after storage - weight of molded product before storage) / (weight of molded product before storage)} x 100
[0110] [Table 1]
[0111] From the results shown in Table 1, it was confirmed that the resin compositions of Examples 1 to 7, in which the content of metal elements belonging to Group 2 was 0.01 mass % or more and 2.0 mass % or less, suppressed the generation of corrosive gases and produced molded articles that maintained their abrasion resistance under high temperature and high humidity conditions.
[0112] In addition, it was also confirmed that the resin compositions of Examples 1 to 5 and 7, in which the content of metal elements belonging to Group 2 is 0.05 mass % or more and 1.5 mass % or less, have a small color difference ΔE under high temperature and high humidity conditions and are less likely to cause color change.
[0113] The resin composition of Comparative Example 1, which did not contain a metal element belonging to Group 2, resulted in a small amount of corrosive gas generated. The resin compositions of Comparative Examples 2 to 4, in which the content of metal elements belonging to Group 2 exceeded 2 mass %, resulted in poor abrasion resistance of the molded articles under high temperature and high humidity conditions.
Claims
1. A resin composition containing a liquid crystal polyester resin, a fluororesin, and an oxide of a metal element belonging to Group 2 of the long periodic table, and not containing a fibrous filler, A resin composition, wherein the content of the metal element belonging to Group 2 is 0.01% by mass or more and 2.0% by mass or less with respect to 100% by mass of the total mass of the resin composition.
2. The resin composition according to claim 1, wherein the content of the metal element belonging to Group 2 relative to 100 parts by mass of the fluororesin is 0.04 parts by mass or more and 8 parts by mass or less.
3. The resin composition according to claim 1 or 2, wherein the content of the oxide of the metal element belonging to Group 2 is more than 0.01 mass% and less than 3.0 mass% with respect to 100 mass% of the total mass of the resin composition.
4. The resin composition according to claim 1 , wherein the content of the fluororesin is 10 parts by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the liquid crystal polyester resin.
5. The resin composition according to claim 1 , wherein the metal element belonging to Group 2 is at least one selected from the group consisting of calcium and magnesium.
6. The resin composition according to claim 5 , wherein the metal element belonging to the second group is calcium.
7. The resin composition according to claim 1, wherein the liquid crystal polyester resin has a repeating unit represented by the following formula (1), a repeating unit represented by the following formula (2), and a repeating unit represented by the following formula (3). (1)-O-Ar 1 -CO- (2)-CO-Ar 2 -CO- (3)-X-Ar 3 -Y- [In formulas (1) to (3), Ar 1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar 2 and Ar 3 each independently represents a phenylene group, a naphthylene group, a biphenylylene group, or a group represented by the following formula (4), and X and Y each independently represent an oxygen atom or an imino group (-NH-). 1 , Ar 2 Or Ar 3 One or more hydrogen atoms in the group represented by the formula (I) may be substituted, independently of one another, with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.] (4)-Ar 4 -Z-Ar 5 - [In formula (4), Ar 4 and Ar 5 each independently represents a phenylene group or a naphthylene group, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylidene group having 1 to 10 carbon atoms. 4 Or Ar 5 One or more hydrogen atoms in the group represented by the formula (I) may be substituted, independently of one another, with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.]
8. A molded article comprising the resin composition according to claim 1.
9. A sliding member comprising the molded article according to claim 8.
Citation Information
Patent Citations
Liquid-crystal polyester resin composition
JP1998025402A